The influence of reputation on supplier selection: An empirical study of the European automotive industry. Issue 1 (January 2019) - Manello, Alessandro; Calabrese, Giuseppe
Abstract: Using an original database, integrated with information by the web, we propose an ex-post analysis on the main factors influencing the selection process of tier 1 suppliers in the automotive industry. There is plenty of literature on how buyers should select their suppliers, but the literature on how they really do so is scarce. We contribute analysing an original database collecting purchasing contracts information within the automotive components market in Europe. We investigate, through different econometric approaches the influence of traditional supplier selection criteria in combination with different reputation factors. Our findings suggest that reputation plays a crucial role more than classical criteria; in particular, suppliers, which serve a diversified customer portfolio or with strong exposure to premium brand customers have better chances to gain additional orders and broaden their customer base even more. The latter means that OEMs have to increase their reputation in order to be more attractive for suppliers. Highlights: We propose an ex-post analysis on the main factors influencing supplier selection. We focus on purchasing contracts of cars assembled in European plants. We find that reputational factors show a positive effect on supplier selection. Supplier selection criteria are strongly influenced by market features.